Aesthetic rehabilitation with crowns and laminate veneers on maxillary anterior teeth and altered cast impression technique for mandibular metal framework partial denture - Mia Syafitri; Meliana; Akmal S. Ikhwan; Andrian T. (Indonesian Journal of Prosthodontic, 2025)
ABSTRACT Introduction: Partial tooth loss in the mandible can impair masticatory function, phonetics, and occlusal stability, and reduce quality of life. Discoloration and disharmony in the shape of the maxillary anterior teeth also affect smile esthetics and self-confidence. A combination of veneers and crowns on the maxillary anterior teeth with a metal-framework removable partial denture in the mandible is a functional and relatively affordable prosthodontic rehabilitation option. Case Report: A 46-year-old female patient presented to the Dental and Oral Hospital of Hasanuddin University with a chief complaint of feeling insecure about her appearance due to the shape of her teeth and various teeth in the maxilla. The patient also complained of difficulty chewing due to the loss of several teeth in the mandible. She had never used any dentures before. The patient requested a denture that could improve her appearance and be comfortable so that she could chew food properly. Conclusion: Rehabilitation using a combination of crowns and laminate veneers on the maxillary anterior teeth and a metal-framework removable partial denture (RPD) with the Altered Cast technique in the mandible successfully improved aesthetics, occlusal function, and patient comfort. This approach provides more stable prosthesis adaptation, natural restorative results, and good clinical success. Comprehensive care and periodic control are required to maintain long-term results. Keywords: Veneer, crown, Metal framework, Removable Partial Denture, Partially Edentulous, Altered Cast Technique